ANALISIS PENGEMBANGAN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) GURU SOSIOLOGI DI SMA KEMALA BHAYANGKARI SUNGAI RAYA - Jabarkis Jabarkis; Sulistyarini Sulistyarini; Imran Imran (Universitas Tanjungpura, 2020)
AbstractThis research is intended to find out the process of developing a lesson plan for sociology teachers at SMA Kemala Bhayangkari Sungai Raya. The approach of this research is a qualitative approach, and the method is a descriptive method. The researcher used observation, interview, and documentation as the techniques of data collection. Furthermore, the analysis in this research was presented in a descriptive qualitative which deals with 3 informants, they are the sociology teachers from SMA Kemala Bhayangkari Sungai Raya. The result showed that the aspects of the syllabus development, the identification of material, objective, model, method, strategies, assessment, and the time allocation were had been done successfully based on each indicators. However, there are still some aspects that need to be fixed in the lesson plan that will be used by the teachers. Consequently, the development of the lesson plan will be well develop, and it will be able to be used in teaching and learning process.Key words: Development, Lesson plan, Sociology, Teachers